Sosialisasi dan Pendampingan Pembukuan Laporan Setoran Hasil Panen Sederhana pada Usaha Warung Sayur Bu Karti - Putri Nur Intan Fazrina; Mirza Andrian Syah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Vegetable traders are the occupation of the majority of the people in Claket Village, Pacet District, Mojokerto. The lack of knowledge and insight gained by vegetable traders regarding the recording of vegetable deposits so that there is no accurate recording or data on vegetable deposits. Community service activities are carried out by providing outreach and assistance to provide insight and application of accounting reports. This activity consists of four stages, namely the planning stage, the preparation stage, the socialization stage and the mentoring stage. The existence of socialization and assistance is expected to help vegetable traders in managing their bookkeeping.